Is hip morphology a risk factor for developing hip osteoarthritis? A systematic review with meta-analysis. Issue 9 (September 2021) - Casartelli, N.C.; Maffiuletti, N.A.; Valenzuela, P.L.; Grassi, A.; Ferrari, E.; van Buuren, M.M.A.; Nevitt, M.C.; Leunig, M.; Agricola, R.
Summary: Objective: To appraise the highest evidence on hip morphology as a risk factor for developing hip osteoarthritis (OA). Design: We searched for studies evaluating the association between radiological hip morphology parameters and the prevalence, incidence or progression of hip OA (based on different radiographic and clinical criteria) in the MEDLINE, EMBASE, Web of Science, Scopus, Cochrane Library and PEDro databases from inception until June 2020. Prospective and cross-sectional studies were separately evaluated. Data are presented as odds ratios (OR) with 95% confidence intervals (CI). Results: We included 9 prospective and 21 cross-sectional studies in the meta-analysis, and evaluated 42, 831 hips from 25, 898 individuals (mean age: 59 years). Prospective studies showed that, compared with control hips, hips with cam morphology (alpha angle >60°; OR = 2.52, 95% CI: 1.83 to 3.46, P  < 0.001) or hip dysplasia (lateral center-edge angle (LCEA) <25°; OR = 2.38, 95% CI: 1.84 to 3.07, P  < 0.001), but not hips with pincer morphology (LCEA >39°; OR = 1.08, 95% CI: 0.57 to 2.07, P  = 0.810), were more likely to develop hip OA than hips without these morphologies. Cross-sectional studies showed a greater prevalence of pincer morphology (LCEA >39°, OR = 3.71, 95% CI: 2.98 to 4.61, P  < 0.001) and acetabular retroversion (crossover sign; OR = 2.65, 95% CI: 1.17 to 6.03, P  = 0.020) in hips with OA than in control hips. Conclusion: Cam morphology and hip dysplasia were consistently associated with the development of hip OA. Pincer morphology was associated with hip OA in cross-sectional but not in prospective studies. The heterogeneous quantification of pincer morphology on radiographs limits a clear conclusion on its association with hip OA.